2020
DOI: 10.1177/1089268020918843
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Everyday Prospection: A Review and Theoretical Integration of Research on Mind-Wandering, Future Thinking, and Prospective Memory

Abstract: The ability to imagine and simulate events that may happen in the future has been studied in several related but independent research areas (e.g., episodic future thinking, mind-wandering, prospective memory), with a newly emerging field of involuntary future thinking focusing primarily on the spontaneous occurrence of such thoughts. In this article, we review evidence from these diverse fields to address important questions about why do people think about the future, what are the typical and most frequent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 121 publications
(233 reference statements)
6
64
0
Order By: Relevance
“…Evidence for this can be found across a range of recent studies on spontaneous future thinking. The most important and direct evidence comes from those laboratory and naturalistic experiencesampling studies that have specifically examined the content of participants' spontaneous future thoughts (for a review of these studies, see Kvavilashvili & Rummel, 2019). For example, using a laboratory vigilance task with probes in which participants had to describe their thoughts at that moment, Plimpton et al (2015) showed that plans and intended actions (e.g., "I remembered that I need to book some days out with friends and for myself", "I must text X for a dinner date") made up a large percentage (60%) of spontaneous future thoughts.…”
Section: Spontaneous Future Thinkingmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence for this can be found across a range of recent studies on spontaneous future thinking. The most important and direct evidence comes from those laboratory and naturalistic experiencesampling studies that have specifically examined the content of participants' spontaneous future thoughts (for a review of these studies, see Kvavilashvili & Rummel, 2019). For example, using a laboratory vigilance task with probes in which participants had to describe their thoughts at that moment, Plimpton et al (2015) showed that plans and intended actions (e.g., "I remembered that I need to book some days out with friends and for myself", "I must text X for a dinner date") made up a large percentage (60%) of spontaneous future thoughts.…”
Section: Spontaneous Future Thinkingmentioning
confidence: 99%
“…Further evidence for the 'pre-made' hypothesis of spontaneous future thoughts and why they come to mind rapidly , comes from studies that have compared the temporal distribution of thoughts. Thus, compared to voluntary future thoughts, spontaneous future thoughts are often about temporally near events referring to tasks and events occurring later in the same day or in the next few days (for a review, see Kvavilashvili & Rummel, 2019; see also Berntsen, 2019, for a re-analysis of data from three studies). Presumably, concrete and previously constructed plans would likely refer to temporally near happenings, and this accords with data from several studies (Berntsen & Jacobsen, 2008;Plimpton et al, 2015).…”
Section: Spontaneous Future Thinkingmentioning
confidence: 99%
See 3 more Smart Citations